MASALAH PRIORITAS DALAM USAHATANI KANGKUNG ORGANIK DI KELOMPOK TANI NEKAF MESE BAUMATA TIMUR KECAMATAN TAEBENU KABUPATEN KUPANG - Febronius Rikarno Talan; Charles Kapioru; Selfius P. N. Nainiti; Marthen Robinson Pellokila (Undana Press, 2023)
This research aimed to determine the ability of farmers in applying the methods or techniques of kangkung cultivation and the priority issues faced by kangkong farmers. Kupang Regency was chosen as a research site because there were kangkong farmers working with markets. This research used a case research method, and the type of data collected consists of primary data and secondary data, the data collection starts from December to January 2021, the data analysis uses Likert scaling analysis. The measured variables were problems related to aspects of kangkong cultivation. The results showed that the cultivation of kangkong (Ipomea reptans poir) at the research site was not done well, as it was still being grown seasonally and using only farmland. So it really needs agricultural extension when applying these 7 aspects. The eradication of pests and diseases was a priority problem for farmers in organic Kangkung vegetable cultivation in Baumata Timur Village, Taebenu District, Kupang Regency, where the mean level of interest was above the All Mean value (2.56 > 2.48) and the average ability level was lower than the overall average skill level (2.36 < 2.4).